Communication virtues in patient-physician relationship - Ricci, Elena (Medicina e Morale, 2020)
For a long time, communication has been considered as a secondary issue in medicine, negatively affecting the patient- physician relationship. Many studies show this, analyzing the aspects complained by patients about health care practices. Among the main, we find the lack of a good communication relationship with the doctor. To make up for this problem, increasingly flourishing literature has tried to deepen the aspect of communication in the health field, showing the problems that this lack can create in medical practice (e.g. a reduced trust in physicians can damage the therapeutic alliance between a health care professionals and a patient). A no less flourishing production has tried to enlighten whether there are particular traits of character that, properly cultivated, encourage the health care professionals' good acting. However, curiously, these two areas have been only indirectly correlated. The aim of this paper is to illustrate the link between them, showing the importance of the communicative aspect in medical practice and highlighting how much the results of a good patient-physician relationship depends on the health care professionals' caring manner. For this reason, using Virtue Ethics, in the last paragraph of this work I propose a list of virtues that, growing in the physician, can make the communicative practice a good practice, attentive to the patient's needs.